The use of diacritised letters in yorùbá text messaging among mobile phone users in Òyọ́ East Local Government Area of Nigeria (2017)
This study investigated the awareness and use of diacritics in Yorùbá text messaging. Guided by the Technology Acceptance Model (TAM) and Gardner’s Socio-educational Model, the study used the questionnaire and Focus Group Discussion guide to gather data from 230 purposively selected mobile phone users in Òyó East Local Government Area of Nigeria. Findings revealed that although most of the respondents were aware of the diacritic feature on their mobile phones and had a favourable disposition towards the use of Yorùbá language in text messaging, they did not perceive the usefulness of diacritics in text messaging. They considered the use of diacritised letters as laborious and unnecessary. The study therefore recommended that the use of diacritics in Yorùbá text messaging should be given adequate attention by scholars and development communication experts as the SMS could serve as a platform for the development of the Yorùbá Language.